(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The systematic management of infectious diseases spans a complex continuum ranging from initial outbreak control to regional elimination and, ultimately, global eradication. Navigating these distinct phases requires sophisticated decision-making tools that can dynamically balance epidemiological necessities with severe socioeconomic constraints. While traditional epidemiological models have provided foundational insights into pathogen transmission, they frequently struggle to incorporate the stochastic nature of human behavior, economic vulnerabilities, and real-world resource limitations.